2019
DOI: 10.1002/jgc4.1129
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling job market in the United States and Canada: An analysis of job advertisements 2014–2016

Abstract: Genetic counseling careers continue to evolve, yet there remains a lack of information about hiring trends in the genetic counseling profession. In this study, job advertisements in the United States and Canada were analyzed, using the National Society of Genetic Counselors (NSGC) Job Connections and the American Board of Genetic Counseling (ABGC) eBlasts from 2014 to 2016 to appraise job roles, qualifications, settings, specialties, and type. NSGC had 1875 advertised openings from 2014 to 2016, while ABGC had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Thus, our model’s 2020 estimated need for 53 GMDs and 200 GCs working in direct patient care in cancer represents approximately 50% of the available genetics workforce. This is consistent with other studies that have shown that cancer accounts for a large number of patients seen in genetics clinics [ 4 ] and is the most common practice area for new GCs [ 6 , 20 ]. However, considering that there are only about 20–25 graduates from Canadian genetic counseling programs per year [ 21 ], with only about 10–12 choosing a cancer specialty, Canadian genetics clinics may struggle to meet the base case’s projected need for an additional 129 GCs by 2030.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our model’s 2020 estimated need for 53 GMDs and 200 GCs working in direct patient care in cancer represents approximately 50% of the available genetics workforce. This is consistent with other studies that have shown that cancer accounts for a large number of patients seen in genetics clinics [ 4 ] and is the most common practice area for new GCs [ 6 , 20 ]. However, considering that there are only about 20–25 graduates from Canadian genetic counseling programs per year [ 21 ], with only about 10–12 choosing a cancer specialty, Canadian genetics clinics may struggle to meet the base case’s projected need for an additional 129 GCs by 2030.…”
Section: Discussionsupporting
confidence: 92%
“…To (Burns, et al, 2019). This is in addition to the fact that recent genetic counseling graduates may be less likely to pursue non-patient-facing roles compared to those with more years of experience.…”
Section: Study Limitationsmentioning
confidence: 99%
“…In 2008, 82% of counselors reported working in clinical settings and providing direct patient care [6], dropping to 59% in 2018 [5] and 2019 [7]. With a wider range of job opportunities in administration, research, public health, industry, and public policy [8], the number of counselors practicing in clinical settings is declining [7,9].…”
Section: Introductionmentioning
confidence: 99%